Combining attachment-based family therapy and cognitive behavioral therapy to improve outcomes for adolescents with anxiety - Herres, Joanna; Krauthamer Ewing, E. Stephanie; Levy, Suzanne; Creed, Torrey A.; Diamond, Guy S. (Frontiers in Psychiatry, 2023)
Increases in adolescent anxiety over the past several years suggest a need for trauma-informed, culturally responsive interventions that help teens cope with environmental stressors like those associated with the COVID-19 pandemic. Although abundant evidence supports the efficacy of cognitive behavioral therapy (CBT) in treating adolescent anxiety, not all teens respond positively to CBT. CBT does not typically include strategies that address important family factors that may be impacting the teen’s functioning, such as the attachment relationship. Attachment-based family therapy (ABFT) addresses the attachment relationship and other factors that contribute to the adolescent’s anxiety and related distress. By enhancing positive parenting behaviors, such as acceptance and validation of the adolescent’s distress and promotion of their autonomy, ABFT sessions may repair the attachment relationship and increase the family’s ability and willingness to engage in CBT tasks aimed at reducing anxiety. This theoretical paper describes the ABFT model and proposes that implementing ABFT sessions prior to CBT could result in better clinical outcomes for adolescents with anxiety disorders by improving the context within which the anxiety symptoms and treatment are experienced. Given that ABFT is sensitive and responsive to family and other contextual factors, adolescents from marginalized communities and those from less individualistic cultures may find the model to be more acceptable and appropriate for addressing factors related to their anxiety. Thus, a combined ABFT+CBT model might result in better outcomes for adolescents who have not historically responded well to CBT alone.